Anosognosia para as discinesias induzidas por levodopa em pacientes com doença de Parkinson - Raphael de Paula Doyle Maia (2016)
Background: Levodopa-induced dyskinesia (LIDs) are the most common side effects of long-term dopaminergic treatment in Parkinsons disease (PD). Some studies have suggested that PD patients may be partially or even completely unaware (anosognosia) of the presence of LIDs. Objectives: To evaluate the factors and possible mechanisms associated with anosognosia for LIDs in patients with PD using movie presentations and mirror self-images. Methods: Thirty patients (15 with LIDs and 15 without LIDs) and 15 healthy volunteers (HVs) were enrolled. Patients were video-recorded and awareness of LIDs was evaluated through videos and mirror self-image. Patients, caregivers and a movement disorder specialist rated both instruments. Neurological assessment included the Unified Parkinsons Disease Rating Scale, the Unified Dyskinesia Rating Scale, the Mini-Mental State Examination, the Montreal Cognitive Assessment, the Beck Depression Inventory, the Beck Anxiety Inventory, the Semantic and Phonologic Verbal Fluency Tests, the Digit Span Task, the Clock Drawing Test. Results: Two patients (13.3%) completely denied the presence of LIDs even after the instructional video exhibition. Since both individuals had chosen the correct video example at the first part of the study, they were classified as having anosognosia that is, they were not able to recognize LIDs in themselves but could do it on others. Six patients (40%) significantly underestimated their LIDs when body parts were taken into account. Three (21.4%) caregivers, in their turn, also demonstrated difficulty in recognizing LIDs in this step, especially when movements were mild. Awareness of LIDs was different between mirror and video among patients and their caregivers: video was superior to the mirror self-images to improve awareness of LIDs. In summary, 8 patients (53.3%) showed decreased awareness of LIDs throughout the study. Lastly, poor self-awareness did not correlate with cognitive tests and psychiatric scales.. Conclusions: Results confirm that anosognosia of the presence of LIDs are common. Therefore, the assessment of dyskinesia in PD patients needs a meticulous interview and, if possible, with the support of visual aids.